(3Qhfb GdCdaGX deYLe GdMaGXs - (3jhSa Hf TGgjf GdcQcj, CHh GdeMGSH, LeGd GdOjf, SHW CMeO Hf MLQ GdYSbdGfj,J (B899 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMajX GdYdje s
(3BNQgG (B:s
(3JQLeI YeQ Hf GdNWGH CejQ GdeDefjf s
(3GdfSNI YdjgG JbQjX ddcGajLi GdMfai SfI (B871 (3HNWgs
(3JcQQ CjVkG JMJ Qbe (B" 689" (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B304s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B148 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs